2005
DOI: 10.1021/jp051188h
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Basis Sets with 11-Electron Analytic Effective Core Potentials of Gold for Modeling Molecular Electronic Devices

Abstract: Three types of 11-electron analytic effective core potentials (ECPs) and their corresponding double-zeta and single-zeta basis sets of gold are evaluated using density functional theory (DFT) calculations. We find that, compared with basis sets derived for use with Hatree-Fock-based Los Alamos (LANL1) and Ermler-Christiansen (EC) ECPs, the DFT-derived Troullier-Martins (TM) ECP together with a single-zeta basis set (TMSZ) is more suitable to describe not only the interaction between gold atoms with a benzene-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 49 publications
(107 reference statements)
0
11
0
Order By: Relevance
“…The BO À anion is isoelectronic with cyanide, CN À , and has been proposed as a possible ligand, or a crystal anion. 46,47 Now, in a study of laser vaporized 10 B/Au samples, the group of Lai-Sheng Wang 48 identified, using mass selection and PES, the species Au n BO À ; n = 1-3. The species Au 2 BO À (C Nv , AuBO and Au 3 BO have closed-shell structures.…”
Section: B: Coordination To Goldmentioning
confidence: 99%
“…The BO À anion is isoelectronic with cyanide, CN À , and has been proposed as a possible ligand, or a crystal anion. 46,47 Now, in a study of laser vaporized 10 B/Au samples, the group of Lai-Sheng Wang 48 identified, using mass selection and PES, the species Au n BO À ; n = 1-3. The species Au 2 BO À (C Nv , AuBO and Au 3 BO have closed-shell structures.…”
Section: B: Coordination To Goldmentioning
confidence: 99%
“…Application of small-core ECPs (19-electron ECP) can minimize errors in the treatment of electron correlation. 70 Similarly, for the gold−DNA combined system (for conventional binding energy (BE) calculation), the B3PW91 level of theory and mixed basis sets (i.e., GenECP/SDD for the Au and 6-31+G(d) for light atoms) are used. Subsequent frequency analysis is also performed on every structure to ensure that no imaginary frequency is present (i.e., minimum energy structure has been achieved in potential energy surface).…”
Section: Computational Detailsmentioning
confidence: 99%
“…For other atoms (in nucleobase and base pairs), 6-31+G­(d) basis sets are used. Application of small-core ECPs (19-electron ECP) can minimize errors in the treatment of electron correlation . Similarly, for the gold–DNA combined system (for conventional binding energy (BE) calculation), the B3PW91 level of theory and mixed basis sets (i.e., GenECP/SDD for the Au and 6-31+G­(d) for light atoms) are used.…”
Section: Computational Detailsmentioning
confidence: 99%
“…This approach allows us to separate the “contact−device−contact” open system into a physically interesting “device” subspace and a “contact” subspace such that the computation can be focused on the device part incorporating the effects of the outside world (“contact”) through appropriately defined self-energy matrices and standard quantum chemistry techniques can be employed in the analysis of the electronic structure of a finite-sized device subspace. However, the NEGF method based on density functional theory (DFT) includes approximations in describing the non-Hermitian self-energy and Green's function, using the real DFT exchange-correlation potential and an incomplete basis set. , In this paper, the contacts and the devices are described by using the LanL2DZ basis set , incorporating relativistic core pseudopotentials because the LanL2DZ basis set provides a good description of the contact surface density of states around the Fermi level and Perdew−Wang 91 correlation because the B3PW91 functional has been proven to be suitable for metal−organic complexes in several studies. …”
Section: Theoretical Formula and Computational Detailsmentioning
confidence: 99%
“…However, the NEGF method based on density functional theory (DFT) includes approximations in describing the non-Hermitian self-energy and Green's function, using the real DFT exchange-correlation potential and an incomplete basis set. 44,45 In this paper, the contacts and the devices are described by using the LanL2DZ basis set 46,47 incorporating relativistic core pseudopotentials because the LanL2DZ basis set provides a good description of the contact surface density of states around the Fermi level. 48 And the self-consistent potential is calculated by using DFT with Becke-3 exchange 49 and Perdew-Wang 91 correlation 50 because the B3PW91 functional has been proven to be suitable for metal-organic complexes in several studies.…”
Section: Theoretical Formula and Computational Detailsmentioning
confidence: 99%